New insights into the functional morphology of calceoli in Amphipoda (Crustacea) - Timm, Roxana; Kerbl, Alexandra; Lörz, Anne-Nina (Zoomorphology, 2024)
Calceoli are putative sensory organs which are known in limnic, marine, and subterranean amphipods for almost 200 years. Despite an otherwise comprehensive understanding of the sensory organs of crustaceans, we still have not unambiguously understood their function. Since calceoli are mainly found on the antennae of male animals, previous studies suggested a chemosensory function mainly related to reproduction. Here, we use a combination of light and electron microscopic techniques to examine the calceoli of Gammarus locusta (Linnaeus 1758) and Oediceroides calmani (Walker 1906), to provide an overview over these structures, and in addition reveal nervous tissue in close proximity to the calceoli. The calceoli of both species are cuticular structures and consist of proximal and distal elements, a stalk and a receptacle that connects both regions. The two studied calceoli differ in the structure of their proximal and distal element, as well as in their receptacle. This study provides new insight into the functional morphology of the antenna and calceolus. Histological sections through the antennae and the calceoli indicate that the calceoli might possess a mechanosensory function.